The chosen will become herds: studies in twentieth-century Kabbalah - Garb, Yehonatan (Yale University Press, 2009)
A noted expert on Kabbalah, Jonathan Garb places the 'kabbalistic Renaissance' within the global context of the rise of other forms of spirituality, including Sufism and Tibetan Buddhism